Senegal : Fourth Review Under the Policy Support Instrument and Second Review Under the Exogenous Shocks Facility-Staff Report; Press Release. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses findings of the Fourth Review Under the Policy Support Instrument and findings of the Second Review Under the Exogenous Shocks Facility for Senegal. All quantitative assessment (performance) criteria were met, notably the targets for the fiscal deficit and the budgetary float. Fiscal policy was tighter during the first half of 2009 than foreseen in the program owing to delays in financing. Structural reforms are broadly on track. The economic rebound in 2010 is projected to be gradual, tracking the global recovery, provided the domestic reform momentum does not slip.